Die IR-Spektren einiger Arsenat-Halogen-Apatite - Manca, Silvia G. (1980)
The infrared spectra of orthoarsenates with apatite structure, of the formulaM5(AsO4)3X (M=Ca, Sr, Ba, Pb andX=F, Cl,Br) are measured and interpreted on the basis of a site-symmetry analysis. The influence of the different cations on the internal vibrations of the AsO34-ions is discussed.